THE IMPLEMENTATION OF SMALL MEDIUM ENTERPRISES FOR ERADICATING UNEMPLOYMENT IN DISTRICT AREA CASE STUDY : LABOR ABSORPTION IN MUNICIPALITIES OF KEDIRI FOR THE PERIOD 2015 - Matahari, Mazaya (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
A high number of job seeker not followed with sufficient number of job vacancies will make an unemployment rate rising in every year. One sector that is recognized for being flexible and helpful in reducing the unemployemnt rate is Small Medium Enterprises. The role of Small Medium Enterprise on economic growth in Indonesia cannot be doubted anymore since it was proven as the best solution for reducing the unemployment during economic crisis at 1998. After that year, Small Medium Enterprise is becoming the main concern to government seeing the market nowadays is dominated with small enterprises. The researcher takes the sample from Kediri that is known with positive improvement of its small enterprises. Type of data used in this research is secondary data. The dependent variable examined in this research is capital, wage, age of business, and SME’s revenue to see their impact on labor absorption in Kediri. The result findings is wage and SME’s Revenue is simultaneously affecting labor absorption in Kediri, while capital and age of business not significantly affecting the labor absorption in Kediri.Keywords: SME, wage, labor absorption, capital, age of business, revenue.